Measuring Government Expenditure Efficiencies Towards Peace and Human Development - Prasetyo, Ahmad Danu; Pudjono, Alpha Nur Setyawan (The Asian Journal of Technology Management (AJTM), 2013)
In this paper, we investigate the efficiency level of government expenditure in 82 countries towards the human development and peace index of the respective countries by using Data Envelopment Analysis (DEA) approach during 2007-2011. We found that only few countries that always being positioned in the efficient frontier during the sample period, namely: Japan, Nigeria, and Norway.Â  By using Malmquist index approach, we also found that Cyprus has the largest government expenditure efficiency improvement.Keywords: Government Expenditure Efficiencies, Human Development Index, Global Peace Indexdoi:10.12695/ajtm.2013.6.2.3Â How to cite this article:Prasetyo, A.D., and Pudjono, A.N.S. (2013). Measuring Government Expenditure Efficiencies Towards Peace and Human Development. The Asian Journal of Technology Management 6 (2): 82-91. Print ISSN: 1978-6956; Online ISSN: 2089-791X. doi:10.12695/ajtm.2013.6.2.3